Thermal study of cyclopalladated complexes of the type [Pd-2(dmba)(2)X-2(bpe)] - (X=NO3-, Cl-, N-3(-), NCO-, NCS-; bpe=trans-1,2-bis(4-pyridyl)ethylene) - De Almeida, E. T.; Santana, A. M.; Netto, AVG; Torres, C.; Mauro, A. E. (Springer, 2005)
The synthesis, characterization and thermal analysis of the novel cyclometallated compounds [Pd-2(dmba)(2)Cl-2(mu-bpe)] (1), [Pd-2(dmba)(2)(N-3)(2)(mu-bpe)] (2), [Pd-2(dmba)(2)(NCO)(2)(mu-bpe)] (3), [Pd-2(dmba)(2)(SCN)(2)(mu-bpe)] (4), [Pd-2(dmba)(2)(NO3)(2)(mu-bpe)] (5) (bpe=trans-1,2-bis(4-pyridyl)ethylene; dmba=N,N-dimethylbenzylamine) are described. The thermal stability of [Pd-2(dmba)(2)X-2(mu-bpe)] complexes varies in the sequence 1 > 4 > 3 > 2 > 5. The final residues of the thermal decompositions were characterized as metallic palladium by X-ray powder diffraction.
Keywords: cyclopalladated complexes; DTA; pseudohalides; TG